Charitable Endowment and Social Change: Cy-Près Orders and Schemes, 1837–1901. Issue 1 (2nd January 2020) - Mitchell, Charles
ABSTRACT: The article discusses the law governing cy-près applications of charitable endowment during the Victorian period and the institutional framework within which cy-près orders and schemes were made. Powers to make such orders and schemes were vested in the court of chancery and the charity commissioners, a body of administrative officials created in 1853. Some case-studies are undertaken, to gain a better understanding of the approaches taken by the court and the commissioners towards the making of orders and schemes and of their opinions regarding certain social, religious and political issues.